Pseudomonas aeruginosa Detection Using Conventional PCR and Quantitative Real-Time PCR Based on Species-Specific Novel Gene Targets Identified by Pangenome Analysis - Wang, Chufang; Ye, Qinghua; Jiang, Aiming; Zhang, Jumei; Shang, Yuting; Li, Fan; Zhou, Baoqing; Xiang, Xinran; Gu, Qihui; Pang, Rui; Ding, Yu; Wu, Shi; et al. (Frontiers in Microbiology, 2022)
Mining novel specific molecular targets and establishing efficient identification methods is significant for detecting P. aeruginosa, which can provide a traceability basis for the pollution of P. aeruginosa in food and water. Pan-genome analysis was used to analyze 2017 strains' whole genomic sequences (including 1000 P. aeruginosa strains and 1017 other common foodborne pathogen strains) downloaded from gene databases to obtain novel species-specific genes. A total of 11 novel candidate species-specific targets genes for P. aeruginosa were mined based on pangenome analysis. There are four novel target genes: UCBPP-PA14_00095, UCBPP-PA14_03237, UCBPP-PA14_04976, and UCBPP-PA14_03627 were selected for use ,which had 100% coverage in the target strain and were not present in non-target bacteria.The PCR primers (PA1, PA2, PA3, and PA4) and the qPCR primers (PA12, PA13, PA14, and PA15) were designed based on these target genes to establish detection methods. Among the PCR primers set, the minimum detectability detection limit for DNA was 65.4 fg/µL, and the primers set PA2 of UCBPP-PA14_03237 gene. The detection limit in pure culture without pre-enrichment was 105 colony-forming units (CFU)/mL for primer set PA1, 103 CFU/mL for primer set PA2, and 104 CFU/mL for primer set PA3 and primer set PA4, respectively. Then, the qPCR standard curves were also established based on the novel species-specific targets. The standard curves showed perfect linear correlation, with the R2 values 0.9901 for primer set PA12, 0.9915 for primer set PA13, 0.9924 for primer set PA14, and 0.9935 for primer set PA15, respectively. The minimum detection limits of the real-time PCR assay were 102 CFU/mL for pure cultures of P. aeruginosa. Compared with the endpoint PCR and traditional culture methods, the real-time PCR assay was more sensitive by one or two orders of magnitude. The feasibility of these methods was satisfying in terms of sensitivity, specificity, and efficiency after evaluating 29 ready-to-eat vegetable samples and being almost consistent with the national standard detection method. The developed assays can be applied for rapid screening and detecting pathogenic P. aeruginosa, providing accurate results to inform effective monitoring measures to improve microbiological safety.